THE INFLUENCE OF THE LEVEL OF SOCIAL INTELLIGENCE DEVELOPMENT ON THE CHOICE OF RESPONSE STRATEGY IN CONFLICT SITUATIONS - Olena V. Karapetrova (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
Among the problems of modern psychology, the concept of «social intelligence» and the problems of its study attracts much attention of researchers and practitioners. The study of social intelligence in modern psychological science has a relatively short research history, but numerous studies by scientists have proven its importance in human social life. It is social intelligence that is associated with the success of human life. The scientific interest in the peculiarities of social intelligence formation is largely related to the search for ways of developing a modern integrated personality. The article is devoted to the problem of social intelligence development and the establishment of links between the level of social intelligence development and the choice of strategy for responding to adolescence conflict situations. The concept of social intelligence, its structure and functions, modern approaches to the problem of social intelligence development in young people are considered. Approaches to the interpretation of response strategy concept are revealed and the types of response strategies in a conflict situation are named. The results of empirical study on the influence of social intelligence development on the choice of response strategy in conflict situations are presented. The general level of social intelligence development in the group of young people is assessed as below average. Such indicators point out the need to develop the level of social intelligence in adolescence, which should contribute to the formation of appropriate social competencies of young people. The absence of low indicators of social intelligence in the study group was proved, which may in some way point out the compliance with the age norms of social intelligence and the general mental development of young people in general, as well as the advantage of using compromise strategy by young men. Among the less used strategies are cooperation and conflict avoidance ones, expressed by relatively identical indicators; the least used strategy is the struggle stategy. Positive relationship was established between the level of social intelligence and the strategy of behavior in a conflict situation: the highest level of social intelligence development is correlated with constructive strategies; the lowest level of social intelligence is correlated with unconstructive strategies. The data obtained point out the need for applying psychological and pedagogical measures to develop social intelligence in adolescence. One of the main and optimal means of developing social intelligence is a developmental program, which is defined as a set of group methods of forming skills and abilities of self-knowledge, communication and mutual understanding of people in the group. The objectives of the program are to form an idea of the essence of the process of identification with other people; awareness of identifying oneself with other people; elaborating individual strategies of identification process actualization; the development of prognostic abilities in communication.